Relationship between histological damage, viral load and serum transaminase levels in patients with chronic hepatitis C - Emin ALTIPARMAK; Ülkü SARITAŞ; Engin ALTINTAŞ; Ali TÜREYEN; Dilek OĞUZ; Tülin ŞAHİN (Turkish Journal of Gastroenterology, 2019)
-